Service Quality, Product Quality, Price, Promotion, and Location on Customer Satisfaction and Loyalty in CV. Restu - Akmal, Eri; Panjaitan, Harry Patuan; Ginting, Yanti Mayasari (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
This study aims to analyze the effect of service quality, product quality, price, promotion, and location on CV Restu's customer satisfaction and loyalty. This research is quantitative research by distributing questionnaires to respondents. The population in this study is CV Restu's customers whose numbers cannot be known with certainty. The sample selection method in this study used the incidental sampling method. Determination of the number of samples in the study using the formula Roscoe theory so that the sample in this study amounted to 70 respondents. Data analysis using Structural Equation Modeling (SEM) using SmartPLS 3.0. application. The results of this study indicate that service quality has no significant effect on customer satisfaction, product quality has no significant effect on customer satisfaction, the price has no significant effect on customer satisfaction, the promotion has no significant effect on customer satisfaction, location has no significant effect on customer satisfaction, service quality has no effect significant effect on customer loyalty, product quality has no significant effect on customer loyalty, the price has a significant effect on customer loyalty, the promotion has no significant effect on customer loyalty, location has no significant effect on customer loyalty and customer satisfaction has no significant effect on customer loyalty.